The role of complement activation in immune thrombocytopenia: mechanisms, biomarkers, and targeted therapies - Tasa, Reece, E. S., author; Jeckel, Kimberly, advisor; Popichak, Katriana, committee member (Colorado State University. Libraries, 2026)
One of the many innate immune defenses, the complement system, functions to opsonize, or "tag" threats to the host’s body for destruction, mediate inflammation, and lyse pathogens (eliminate threats). The complement system is a complicated array of proteins that must undergo various cleavages and binding steps to become functional within a host’s immune system. Although this system is tightly regulated by proteins and factors, it can be involved in certain pathologies of the immune system. Immune Thrombocytopenia (ITP) is a disease characterized by autoimmune destruction of host platelets, whose destruction is heavily assisted by involvement of the various complement pathways. There are primary (pITP) and secondary (sITP) classifications of ITP determined by their pathogenesis, which vary in their responsivity to treatment. Low count of platelets that typically function in clot formation results in various symptoms, ranging from minor (petechiae) to life-threatening (intracerebral hemorrhage). In this review of the literature, an analysis of existing research and gaps in knowledge will summarize what areas of the complement system and pITP remain understudied. Sources used for this review of the literature include many recent (2022-present) and older peer reviewed articles, gathered and filtered primarily using the National Institutes of Health (NIH) database. More extensive treatment options and diagnostic techniques will provide a better quality of life for those with pITP, crucial in allowing those with thrombocytopenias to function normally and maintain active lifestyles. A better understanding of how the complement system is involved with autoimmune diseases will lead to the development of inhibitory therapies targeted towards the complement cascade.
Keywords: immune thrombocytopenia; platelet; complement proteins; autoimmune